Potential use of black soldier fly larvae (Hermetia illucens) as an alternative protein in animal feed - Abu Hassim, Hasliza (2024)
The combined effects of a growing human population and increasing demand for sustainable animal protein has led to many research and development related to black soldier fly larvae (bsfl) as an alternative protein source in animal feed. apart from that, the bsfl also rich in lipids, vitamins and minerals, making them a good nutrient source for animal feed. the utilization of bsfl further develops and applies circular economy concepts, using sustainable, non-polluting and efficient biological process in converting organic waste into animal feed, biomass and fertilizer. additionally, bsfl has the potential to reduce the cost of animal feed formulations by partially replacing soybean and/or fish meals. this is one of the primary reasons why insects like bsf are seen as viable alternative protein sources for animal feeds. nevertheless, the use of bsfl in animal feed presents some issues and challenges in terms of processing (small scale vs large scale), variability and sustainability of organic waste as feedstock and consumer acceptance towards the use of insects as feed ingredients. however, this should be considered in the context of the current shortage of protein sources as animal feed and the nutritional value of bsfl, which has important research significance for sustainability of livestock production